A highly scratch-resistant and light-transmitting polypropylene material and its preparation method and application
By combining high-transparent random polypropylene, homopolypolypropylene and high-transparent elastomer materials in polypropylene materials, and using light diffusing agents, nucleating agents and hardening enhancers, the problem of insufficient light transmittance and scratch resistance in smart cockpit applications is solved, and the high light transmittance and scratch resistance are improved.
Patent Information
- Application Number
- CN202311159998.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-11
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-09-11
AI Technical Summary
Polypropylene materials have problems of insufficient light transmittance and scratch resistance in automotive interior applications, especially under the high application requirements of smart cockpits, it is difficult to meet the light transmittance and scratch resistance of the material at the same time.
Highly transparent random polypropylene and homopolymer polypropylene composite materials with high surface hardness are used, and high-transparent elastomer materials are matched. The light diffusing agent and nucleating agent are used to achieve uniform light distribution and crystal size reduction, and the hardening impermeability and scratch resistance of the material are synergistically improved.
The light transmittance of polypropylene material reaches more than 60% under a thickness of 3mm, and has good impact resistance and scratch resistance, meeting the high application requirements of the smart cockpit.
Smart Images

Figure BDA0004440186650000061 
Figure BDA0004440186650000141 
Figure BDA0004440186650000151
Abstract
Description
Technical Field
[0001] The invention relates to a polypropylene material, in particular to a highly scratch-resistant and light-transmissive polypropylene material and a preparation method and application thereof. Background Art
[0002] Polypropylene (PP) is the most widely used non-metallic material in automobiles, with the total vehicle usage exceeding 50 kg. 3 ), the consumption of PP in complete vehicles is believed to continue to rise in the future. The only drawback is that PP has poor low-temperature toughness. When used in automotive interiors, it is necessary to add additional components such as elastomers and mineral powders for modification to improve the overall toughness of the material and avoid cracking during impact. However, the refractive index of the amorphous elastomer component and the semi-crystalline PP material is very different. When superimposed with opaque mineral components, the light transmittance of the material will be greatly reduced and cannot meet the light transmittance requirements of current smart cockpits. What is more important to note is that the surface hardness of PP material is low, and scratches by fingers will leave very obvious scratches, which further becomes a great disadvantage when used in translucent parts.
[0003] As a semi-crystalline polymer, PP material has poor light transmittance due to its large crystal size. The light transmittance of the material is 60-80% at a thickness of 2mm. In the industry, there are two main ways to improve the light transmittance of the material. One is to insert ethylene or butene segments into PP to destroy the regular structure of PP itself, reduce the crystallinity and thus improve the light transmittance. The other is to add a transparent agent, i.e. a nucleating agent, to PP to reduce the crystal size to be smaller than the wavelength of visible light, thereby achieving improved transparency. Of the two approaches, the former will affect the performance of the PP material itself, and the latter is effective in improving the light transmittance of the material but has limitations. Patent CN201911229274 describes a polypropylene composite material with elastomeric resins of different types and mechanisms added to improve the transparency of the material. This method is to reduce the overall crystallinity of the material to improve the light transmittance, which will affect the performance of the PP material itself. Patent CN202110095682 describes a visual high temperature and hydrolysis resistant long glass fiber reinforced polypropylene composite material for automobile water chambers. It mainly uses a nucleating agent to improve the light transmittance of the material, but the addition of long glass fibers will greatly reduce the transparency of the material. In fact, during application, only the liquid level position can be seen, and the real details of the liquid in the water chamber cannot be seen.
[0004] On the other hand, the scratch resistance of polymer materials is actually closely related to the lubricity and hardness of the material surface. Lubricity prevents foreign matter from peeling off or damaging the material surface when it passes through it, and surface hardness gives the material surface strong resilience and rigidity, thus having good scratch resistance. The surface hardness of PP materials is usually around 2B, and even the slightest scratch can leave obvious marks. The scratch phenomenon will be more serious after adding minerals such as talcum powder. There are four main ways to improve the scratch resistance of PP in the industry: (a) Adding polymer materials with higher hardness such as PMMA to improve the surface hardness. Patent CN107286469B describes a spray-free scratch-resistant PP alloy material that uses a transparent ion polymer (Surlyn resin) to improve the scratch resistance of the material surface; however, this type of polymer has strong polarity and poor compatibility with polypropylene materials, and it is easy to cause red light phase separation; (b) By adding high-hardness minerals or metal powders to improve the surface hardness of the material, patent CN106589552A describes a high-hardness plastic that adds metal, graphite, titanium dioxide and glass fiber to greatly improve the hardness of the plastic, but this method greatly reduces the impact performance of the material; (c) By adding a cross-linking agent to the matrix, the polypropylene is cross-linked to improve heat resistance and surface hardness. Patent CN106589552A describes a high-hardness plastic that adds metal, graphite, titanium dioxide and glass fiber to greatly improve the hardness of the plastic, but this method greatly reduces the impact performance of the material; (c) By adding a cross-linking agent to the matrix, the polypropylene is cross-linked to improve heat resistance and surface hardness. CN111073158A discloses a high-hardness polypropylene heat shrink sleeve substrate, which is prepared by adding a cross-linking agent to PP through radiation cross-linking, and the surface hardness of the material can reach a Shore hardness (60D) or above; however, the radiation cross-linking process is complex and difficult to control, not easy to commercialize, and will affect the light transmittance of the material; (d) Scratch resistant agents and lubricants are added to improve the surface lubricity of the material and enhance the scratch resistance. Patent CN201010230064 introduces a matte, scratch-resistant modified polypropylene composite material for automotive interiors, which improves the surface hardness by using high-crystalline PP, and uses high-molecular weight scratch resistant agents and wear-resistant agents polytetrafluoroethylene to modify high-hardness polyethylene to improve surface lubricity and enhance the scratch resistance of the material, but scratch resistant agents have limited effect on improving the scratch resistance of the material surface, and large amounts of addition will affect the light transmittance of the material.
[0005] In addition, the surface coating curing layer method can also well improve the scratch resistance of the material surface. Patent CN106062053B discloses a surface-enhanced transparent substrate, which is characterized in that a silsesquioxane-compatible polymer cured product (mainly covered on the surface of the substrate in the form of a coating composition) is stacked on the transparent substrate to improve the surface hardness of the substrate. However, first of all, this method belongs to a post-modification method and cannot improve the light transmittance and scratch resistance of the substrate itself. Secondly, the cured product described in patent CN106062053B is a compound with high polarity and poor compatibility with non-polar PP materials. It is not strong when applied to PP substrates. The cured layer can be expected to be very easy to peel off. Finally, coating the cured layer to improve the scratch resistance will increase the complexity of the manufacturing process and the production cost will also increase.
[0006] In summary, although predecessors have made great improvements to the light transmittance and scratch resistance of PP materials, it is still very difficult to meet the higher application requirements of the current smart cockpit. Therefore, in order to ensure that the performance of PP materials meets the requirements of automotive interiors and has excellent light transmittance and scratch resistance, it is urgent to develop new high scratch resistance and light transmittance polypropylene materials. Summary of the invention
[0007] In order to solve the above technical problems, the present invention proposes a highly scratch-resistant and light-transmitting polypropylene material and its preparation method and application. The polypropylene material provided by the present invention is preferably a composite of high-transparency random polypropylene and homopolymer polypropylene with high surface hardness, and is matched with a high-transparency elastomeric material. A light diffuser is used to achieve uniform distribution and transmission of light, a nucleating agent is used to reduce the crystal size, and the light transmittance and scratch resistance of the material are significantly improved under the synergistic effect of a hardening and transmittance-enhancing agent, achieving a light transmittance of more than 60% at a thickness of 3 mm, and having good impact resistance.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] A highly scratch-resistant and light-transmitting polypropylene material comprises the following raw materials in parts by weight:
[0010] A) 100 parts of polypropylene;
[0011] B) 5-50 parts, preferably 5-30 parts, more preferably 10-25 parts of polymer elastomer;
[0012] C) 0.05-10 parts of inorganic filler, preferably 0.1-5 parts, more preferably 0.5-5 parts;
[0013] D) 1-50 parts of hardening and permeability enhancing agent, preferably 1-30 parts, more preferably 5-30 parts;
[0014] E) 0.05-1 part of light diffusing agent, preferably 0.1-1 part, more preferably 0.5-1 part;
[0015] F) 0.5-5 parts of scratch resistance agent, preferably 0.5-3 parts, more preferably 1-3 parts;
[0016] G) 0.1-1 part of nucleating agent, preferably 0.5-1 part, more preferably 0.5-0.8 part;
[0017] H) 0.1-10 parts of other additives, preferably 1-8 parts, more preferably 1.5-7 parts;
[0018] I) 1-10 parts of peroxide, preferably 5-10 parts.
[0019] As a preferred embodiment of the present invention, the polypropylene is selected from at least one of homopolypropylene and random polypropylene, preferably a mixture of homopolypropylene and random polypropylene, more preferably a mixture of homopolypropylene and random polypropylene in a mass ratio of (10-50):(50-90);
[0020] Preferably, the melt flow rate of the homopolymer polypropylene is 10-30 g / 10 min at 230° C. and 2.16 kg, and the melt flow rate of the random polypropylene is 1-30 g / 10 min at 230° C. and 2.16 kg;
[0021] Preferably, the random polypropylene is a terpolymer of propylene-ethylene-butene, wherein the ethylene content is 5-20 mol%, the butene content is 3-10 mol%, and the balance is propylene.
[0022] As a preferred embodiment of the present invention, the polymer elastomer is one or more of ethylene-butene copolymer, ethylene-octene copolymer and hydrogenated styrene-butadiene copolymer, and the melt flow rate is 1-30g / 10min at 230°C and 2.16KG.
[0023] As a preferred embodiment of the present invention, the inorganic filler is one or more of calcium carbonate, talc, mica, wollastonite and magnesium sulfate whisker;
[0024] Preferably, the light diffuser is one or more of barium sulfate, white carbon black, and silicone light diffusers; the silicone light diffuser is preferably Samsung SL-200M from South Korea;
[0025] Preferably, the scratch-resistant agent is one or more of erucic acid amides and organic silicones; the erucic acid amides are preferably Croda212 and CrodaER; the organic silicones are preferably LYSI-306C.
[0026] Preferably, the nucleating agent is one or more of organic aromatic phosphates and dibenzylidene sorbitols; preferably at least one of NA-10 and NA-11 of Aidico and Millad 3905 and Millad NX8000 of Milliken;
[0027] Preferably, the other auxiliary agents are arbitrarily selected from antioxidants and light stabilizers; the antioxidant preferably includes a primary antioxidant and a secondary antioxidant, wherein the primary antioxidant is selected from one or more of hindered phenol antioxidants, thioester antioxidants, phenolic antioxidants, and hindered amine antioxidants, more preferably one or more of antioxidant 1010, antioxidant 1076, antioxidant 1016, antioxidant AO300, antioxidant AO736, and antioxidant 944; the secondary antioxidant is selected from phosphite antioxidants and thioether antioxidants, more preferably one or more of antioxidant 168, antioxidant 626, and antioxidant AO-412S; the light stabilizer is preferably selected from one or more of hindered amine light stabilizers, benzophenone light stabilizers, and benzotriazole light stabilizers, more preferably one or more of UV-770, UV-531, and UV-327.
[0028] Preferably, the peroxide is one or more of dicumyl peroxide, dibenzoyl peroxide (BPO), 2,4-dichlorobenzoyl peroxide, di-tert-butylcumyl peroxide, and azobisisobutyronitrile.
[0029] As a preferred embodiment of the present invention, the hardening and permeability enhancing agent is a copolymer of double-bond-containing cage-type polysilsesquioxane and methyl methacrylate, nadic anhydride, and reactive monomers in a molar ratio of 1: (60-950): (5-400): (0.1-100) preferably 1: (60-600): (5-200): (5-15); the reactive monomer is glycidyl methacrylate and / or maleic anhydride;
[0030] Preferably, the double bond-containing cage-type polysilsesquioxane is methacryloxypropyl cage-type polysilsesquioxane (shown in Formula I).
[0031]
[0032] The present invention does not impose any restriction on the source of the methacryloxypropyl cage-type polysilsesquioxane, which can be directly purchased from commercial products, or prepared and synthesized by the direct hydrolysis method provided in the document "Fan Liping et al. Synthesis and Characterization of Octavidin Cage-type Polysilsesquioxane (OvPOSS). Guangdong Chemical Industry 44.11 (2017): 3". The preferred self-synthesized raw material is γ-methacryloxypropyltrimethoxysilane (KH-570).
[0033] As a preferred embodiment of the present invention, the reaction conditions of the double bond-containing cage-type polysilsesquioxane and methyl methacrylate, nadic anhydride, and reactive monomer are as follows: the raw materials are mixed with an initiator in a solvent, and then the temperature is raised to 70-90° C. and stirred for reaction for 10-15 hours to obtain a copolymer;
[0034] Preferably, the initiator is one or more of azobisisobutyronitrile, benzoyl peroxide, and dicumyl peroxide; the amount of the initiator is 1-10 mol% of the molar amount of the cage-type polysilsesquioxane containing double bonds.
[0035] Preferably, the solvent is one or more of tetrahydrofuran, acetone, and ethyl acetate, and the amount of solvent added is 10-30 times the total mass of the double-bond-containing cage-type polysilsesquioxane, methyl methacrylate, nadic anhydride, and reactive monomer raw materials.
[0036] As a preferred embodiment of the present invention, the viscosity average molecular weight of the hardening and permeability enhancing agent is 50,000-500,000 Daltons.
[0037] As a preferred embodiment of the present invention, the light transmittance of the polypropylene material is 60-80% at a thickness of 3.0 mm, the surface pencil hardness is HB to 2H, and the Izod notched impact strength is 15-50 KJ / m at 23°C. 2 , the flexural modulus is 1000-1600MPa.
[0038] A method for preparing the highly scratch-resistant and light-transmissive polypropylene material as described above comprises the following steps:
[0039] The polypropylene, polymer elastomer, inorganic filler, hardening and permeability enhancing agent, light diffuser, scratch resistant agent, nucleating agent, other additives and peroxide are mixed and added into a twin-screw extruder, melt-mixed and extruded to obtain the polypropylene material;
[0040] Preferably, the melt mixing conditions are: melt temperature 220-230° C., rotation speed 50-100 rpm.
[0041] Application of the highly scratch-resistant and light-transmitting polypropylene material as described above or the highly scratch-resistant and light-transmitting polypropylene material prepared by the method described above in automotive interior products, especially in smart cockpit optical components.
[0042] The invention improves the light transmittance and scratch resistance of the polypropylene material by a specially designed hardening and permeability-enhancing agent, mainly by utilizing the easy migration property of POSS to distribute the polymer chain segments of methyl methacrylate and nadic anhydride connected on the side chain on the surface of the material, so as to improve the material performance; at the same time, methyl methacrylate, nadic anhydride and POSS are copolymerized and connected to make up for the loss of impact resistance of the polymer material, so as to achieve enhanced mechanical properties; and by introducing functional groups such as anhydrides and glycidyl esters, the system is chemically cross-linked during the extrusion and blending of the polypropylene material, so as to improve the overall compatibility and ensure the material performance. DETAILED DESCRIPTION
[0043] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.
[0044] For those skilled in the art, the features, benefits and advantages of the present invention will become apparent by reading the disclosure of this specification.
[0045] The main raw material information involved in the following embodiments of the present invention is as follows:
[0046] Methacryloyloxypropyl cage polysilsesquioxane: CAS: 622404-27-7, purchased from TCI (Shanghai) Chemical Trading Co., Ltd.
[0047] Homopolymer polypropylene 1100N: melt flow rate 12g / 10min, purchased from Shenhua Ningmei;
[0048] Homopolymer polypropylene Z30S: melt flow rate 30g / 10min, purchased from Shanghai Secco;
[0049] Random polypropylene RP344RK: melt flow rate 28g / 10min, ethylene content 15mol%, butene content 8mol%, purchased from Northern Huajin;
[0050] Random polypropylene 5012XT: melt flow rate 1g / 10min, ethylene content 15mol%, butene content 5mol%, purchased from Formosa Plastics;
[0051] Polymer elastomer 8200: ethylene-octene copolymer, purchased from Dow Chemical;
[0052] Polymer elastomer 7467: ethylene-butene copolymer, purchased from Dow Chemical;
[0053] Polymer elastomer 4033: hydrogenated styrene-butadiene copolymer, purchased from Kuraray, Japan;
[0054] Talc AH51210L: purchased from Liaoning Aihai;
[0055] Calcium carbonate KL5: purchased from Guangxi Kelong;
[0056] Magnesium sulfate whiskers: purchased from Shanghai Gerunya;
[0057] Light diffuser SL200M: purchased from Samsung, South Korea;
[0058] White carbon black, purchased from China National Pharmaceutical Group;
[0059] Barium sulfate, purchased from Chi Mei Chemical;
[0060] Nucleating agent NA-11: purchased from Aidico;
[0061] Nucleating agent Millad 3905 and nucleating agent Millad NX8000 were purchased from Milliken;
[0062] Scratch resistant agent 306C: organic silicone, purchased from Silike;
[0063] Scratch resistant agent Croda212: erucic acid amide, purchased from Croda;
[0064] Benzoyl peroxide (BPO), diisopropylbenzene peroxide, and azobisisobutyronitrile were purchased from China National Pharmaceutical Group;
[0065] Antioxidant 1010 and antioxidant 168 were purchased from BASF.
[0066] Methyl methacrylate, nadic anhydride, glycidyl methacrylate, maleic anhydride, hydrochloric acid, anhydrous methanol, anhydrous ethanol, acetone, tetrahydrofuran, etc. were purchased from China National Pharmaceutical Group. Other reagents were purchased from commercial sources unless otherwise specified.
[0067] The main test methods involved in the following embodiments of the present invention are as follows:
[0068] Viscosity average molecular weight test method: refer to GBT12005.1-1989 for measuring the molecular weight of polyacrylamide (PAM, hereinafter referred to as PAM), take 200 mg of sample and dissolve it in 20 mL of tetrahydrofuran to prepare a 0.01 g / mL test solution, wash and dry the Ubbelohde viscometer with an inner diameter of 0.6 mm, calibrate it with a standard solvent, record the time t0, wash and dry it again, add an appropriate amount of the test solution as required, and measure t after preheating in a 25°C constant temperature water bath for 20 minutes. Calculate the viscosity average molecular weight Mη by the one-point method formula.
[0069] η r =t / t0
[0070] η sp =(t-t0) / t0
[0071] [η]=[2(η sp -lnη r )] 1 / 2 / C
[0072] M η =([η] / K) 1 / α
[0073] Note: K and α are Mark Houwink parameters, and C is the concentration of polymer solution (g / mL).
[0074] Scratch resistance test: According to the method in standard GMW14688, the L value change of the test sample before and after is ΔL;
[0075] Pencil hardness test: Test according to the method in standard GB6739-2006.
[0076] Uniform light test: Use an LED lamp placed 5 cm behind the sample, and observe the size of the light-transmitting aperture from the back of the sample. If the area is larger than 1 cm, it is good; if the area is smaller than 1 cm and the lamp beads can be seen, it is poor.
[0077] Light transmittance test: According to the standard ISO13468-1, the incident light intensity before and after the sample is tested using a haze meter is T1 and T2 respectively, and the material transmittance is T = T2 / T1;
[0078] Mechanical properties test: tensile strength and flexural modulus are tested according to ISO527; cantilever beam notched impact strength is tested according to ISO180.
[0079] Macro phase separation test: This evaluation is a visual judgment. The material is injection molded into a 60×60×3mm sample and the edges and surfaces of the sample are observed for delamination or peeling. If so, macro phase separation exists.
[0080] The following examples 1-4 and comparative examples 1-4 are used to prepare different hardening and permeability-enhancing agents, respectively.
[0081] [Preparation Example 1]
[0082] Methacryloyloxypropyl cage-type polysilsesquioxane and azobisisobutyronitrile initiator were added to the polymerization tube. After repeated vacuuming and nitrogen filling for three times, methyl methacrylate, nadic anhydride, glycidyl methacrylate and tetrahydrofuran solvent were added respectively. The temperature was controlled at 80°C under sealed conditions and stirred for 12 hours. Among them, the molar ratio of methacryloxypropyl cage-type polysilsesquioxane, methyl methacrylate, nadic anhydride and glycidyl methacrylate was 1:90:10:5. The amount of initiator used was 1% of the molar amount of methacryloxypropyl cage-type polysilsesquioxane.
[0083] After the reaction was completed, the solution was poured into a beaker, and anhydrous methanol was added at room temperature to precipitate the product, which was filtered to obtain a white solid, namely, the hardening and permeability-enhancing agent 1, and the viscosity-average molecular weight of the product was 50,000 Daltons.
[0084] [Preparation Example 2]
[0085] Methacryloyloxypropyl cage-type polysilsesquioxane and benzoyl peroxide initiator were added to the polymerization tube. After repeated vacuuming and nitrogen filling for three times, methyl methacrylate, nadic anhydride, maleic anhydride and tetrahydrofuran solvent were added respectively. The temperature was controlled at 90°C under sealed conditions and stirred for 10 hours. Among them, the molar ratio of methacryloyloxypropyl cage-type polysilsesquioxane, methyl methacrylate, nadic anhydride and maleic anhydride was 1:600:200:10. The amount of initiator used was 5% of the molar amount of methacryloyloxypropyl cage-type polysilsesquioxane.
[0086] After the reaction was completed, the solution was poured into a beaker, and anhydrous methanol was added at room temperature to precipitate the product, which was filtered to obtain a white solid, namely, the hardening and permeability-enhancing agent 2, and the product had a viscosity-average molecular weight of 500,000 Daltons.
[0087] [Preparation Example 3]
[0088] Methacryloyloxypropyl cage-type polysilsesquioxane and dicumyl peroxide initiator were added to the polymerization tube. After repeated vacuuming and nitrogen filling three times, methyl methacrylate, nadic anhydride, glycidyl methacrylate and tetrahydrofuran solvent were added respectively. The temperature was controlled at 70°C under sealed conditions and stirred for 15 hours. Among them, the molar ratio of methacryloyloxypropyl cage-type polysilsesquioxane, methyl methacrylate, nadic anhydride and glycidyl methacrylate was 1:119:6:13. The amount of initiator used was 7% of the molar amount of methacryloyloxypropyl cage-type polysilsesquioxane.
[0089] After the reaction was completed, the solution was poured into a beaker, and anhydrous methanol was added at room temperature to precipitate the product, which was filtered to obtain a white solid, namely, the hardening and permeability-enhancing agent 3, and the product had a viscosity-average molecular weight of 250,000 Daltons.
[0090] [Preparation Example 4]
[0091] Methacryloyloxypropyl cage-type polysilsesquioxane and azobisisobutyronitrile initiator were added to the polymerization tube. After repeated vacuuming and nitrogen filling three times, methyl methacrylate, nadic anhydride, maleic anhydride and tetrahydrofuran solvent were added respectively. The temperature was controlled at 80°C under sealed conditions and stirred for 15 hours. Among them, the molar ratio of methacryloyloxypropyl cage-type polysilsesquioxane, methyl methacrylate, nadic anhydride and maleic anhydride was 1:120:80:5. The amount of initiator used was 10% of the molar amount of methacryloyloxypropyl cage-type polysilsesquioxane.
[0092] After the reaction was completed, the solution was poured into a beaker, and anhydrous methanol was added at room temperature to precipitate the product, which was filtered to obtain a white solid, namely, the hardening and permeability-enhancing agent 4, and the viscosity-average molecular weight of the product was 350,000 Daltons.
[0093] [Preparation of Comparative Example 1]
[0094] The hardening and permeability enhancing agent 5 was prepared in the same manner as in Example 3, except that methyl methacrylate was not added. The product had a viscosity average molecular weight of 6000 Daltons.
[0095] [Preparation of Comparative Example 2]
[0096] The hardening and permeability enhancing agent 6 was prepared in substantially the same manner as in Example 3, except that nadic anhydride was not added. The product had a viscosity average molecular weight of 230,000 Daltons.
[0097] [Preparation of Comparative Example 3]
[0098] The hardening and permeability enhancing agent 7 was prepared in substantially the same manner as in Example 3, except that glycidyl methacrylate was not added and nadic anhydride was replaced with the same molar amount of norbornene. The product had a viscosity average molecular weight of 230,000 Daltons.
[0099] [Preparation of Comparative Example 4]
[0100] The hardening and permeability enhancing agent 8 was prepared in the same manner as in Example 3, except that the molar ratio of methacryloxypropyl cage-type polysilsesquioxane, methyl methacrylate, nadic anhydride, and glycidyl methacrylate was changed to 1:20:1:2. The product had a viscosity average molecular weight of 30,000 Daltons.
[0101] The following Examples 1-9 and Comparative Examples 1-5 are used to prepare different polypropylene materials.
[0102] [Example 1]
[0103] 30 g of polypropylene 1100N, 70 g of RP344RK, 25 g of hardening and permeability enhancer 3, 15 g of elastomer 8200, 5 g of inorganic filler talc, 0.1 g of light diffuser SL200M, 0.5 g of nucleating agent NA-11, 2 g of scratch resistant agent 306C, 5 g of peroxide BPO, 1 g of antioxidant 1010 and 0.5 g of antioxidant 168 were mixed and added into a twin-screw extruder, and melt-mixed and extruded at a melting temperature of 220° C. and a rotation speed of 100 rpm to obtain a polypropylene material.
[0104] [Example 2-9]
[0105] Different polypropylene materials were prepared by the same method as in Example 1, except that the raw material selection and dosage (g) were as disclosed in Table 1.
[0106] [Comparative Example 1]
[0107] Different polypropylene materials were prepared by referring to the method basically the same as that of Example 1, except that the hardening and permeability enhancing agent 3 was replaced by the hardening and permeability enhancing agent 5 provided in Comparative Example 1.
[0108] [Comparative Example 2]
[0109] Different polypropylene materials were prepared by referring to the method basically the same as that of Example 1, except that the hardening and permeability enhancing agent 3 was replaced by the hardening and permeability enhancing agent 6 provided in Comparative Example 2.
[0110] [Comparative Example 3]
[0111] Different polypropylene materials were prepared by referring to the method basically the same as that of Example 1, except that the hardening and permeability enhancing agent 3 was replaced by the hardening and permeability enhancing agent 7 provided in Comparative Example 3.
[0112] [Comparative Example 4]
[0113] Different polypropylene materials were prepared by referring to the method basically the same as that of Example 1, except that the hardening and permeability enhancing agent 3 was replaced by the hardening and permeability enhancing agent 8 provided in Comparative Example 4.
[0114] [Comparative Example 5]
[0115] Different polypropylene materials were prepared by a method substantially the same as that in Example 1, except that the raw material did not contain the hardening and permeability enhancing agent 3.
[0116] The polypropylene materials prepared in Examples 1-9 and Comparative Examples 1-5 were tested for transmittance, hardness, scratch resistance, mechanical properties, etc. The results are shown in Table 2.
[0117] As can be seen from the test results in Table 2, the polypropylene materials prepared by Examples 1-9 of the present invention have good comprehensive performance in terms of tensile strength, flexural modulus, and cantilever beam notched impact strength, and the light transmittance is high, the scratch resistance and the pencil hardness all meet the high use requirements, but the hardening and permeability enhancer in Comparative Example 1 does not add methyl methacrylate, resulting in a significant decrease in the pencil hardness and light transmittance of the material compared with Example 1, while the impact resistance is increased, but the flexural modulus representing rigidity, etc., is decreased, which is not suitable for application in automotive materials. In Comparative Example 2, the hardening and permeability enhancer does not add nadic anhydride, resulting in a decrease in light transmittance, accompanied by a slight macroscopic phase separation. Comparative Example 3 uses a hardening and permeability enhancer 7 without a reactive group, which cannot promote the compatibility of the high-content auxiliary agent with the system, and macroscopic phase separation occurs. In Comparative Example 4, the raw material ratio of the hardening and permeability enhancer is unreasonable, resulting in a small amount of polymerization, a small molecular weight of the polymer, and it is difficult to exert the characteristics of the polymer itself, and it is impossible to show the characteristics of high surface hardness and high light transmittance, and the surface hardness and light transmittance are significantly low. Comparative Example 5 does not contain a hardening and permeability-enhancing agent, and its performance is lower than that of the examples, and cannot meet higher application requirements.
[0118] Table 1, raw material selection and dosage in Examples 1-9 (g)
[0119]
[0120]
[0121] Table 2. Performance test results
[0122]
[0123]
Claims
1. A highly scratch-resistant and light-transmitting polypropylene material, characterized in that: The invention comprises the following raw materials in parts by weight: A) 100 parts of polypropylene; B) 5-50 parts of polymer elastomer; C) 0.05-10 parts of inorganic filler; D) 1-50 parts of hardening and permeability enhancing agent; E) light diffusing agent 0.05-1 part; F) 0.5-5 parts of anti-scratch agent; G) 0.1-1 part of nucleating agent; H) other additives 0.1-10 parts; 1) 1-10 parts of peroxide; The hardening and permeability enhancing agent is a copolymer of double-bond-containing cage-type polysilsesquioxane and methyl methacrylate, nadic anhydride, and reactive monomers in a molar ratio of 1: (60-950): (5-400): (0.1-100); the reactive monomers are glycidyl methacrylate and / or maleic anhydride.
2. The highly scratch-resistant and light-transmitting polypropylene material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: A) 100 parts of polypropylene; B) 5-30 parts of polymer elastomer; C) 0.1-5 parts of inorganic filler; D) adding 1-30 parts of hardening and permeability enhancing agent; E) 0.1-1 part of light diffusing agent; F) 0.5-3 parts of scratch resistant agent; G) 0.5-1 part of nucleating agent; H) 1-8 parts of other additives; 1) 5-10 parts of peroxide.
3. The highly scratch-resistant and light-transmitting polypropylene material according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: A) 100 parts of polypropylene; B) 10-25 parts of polymer elastomer; C) 0.5-5 parts of inorganic filler; D) adding 5-30 parts of hardening and permeability enhancing agent; E) 0.5-1 part of light diffusing agent; F) 1-3 parts of scratch resistant agent; G) 0.5-0.8 parts of nucleating agent; H) 1.5-7 parts of other additives; 1) 5-10 parts of peroxide.
4. The highly scratch-resistant and light-transmitting polypropylene material according to claim 1, characterized in that: The polypropylene is selected from at least one of homopolypropylene and random polypropylene.
5. The highly scratch-resistant and light-transmitting polypropylene material according to claim 4, characterized in that: The polypropylene is selected from a mixture of homopolypropylene and random polypropylene.
6. The highly scratch-resistant and light-transmitting polypropylene material according to claim 4, characterized in that: The polypropylene is selected from a mixture of homopolypropylene and random polypropylene in a mass ratio of (10-50):(50-90).
7. The highly scratch-resistant and light-transmitting polypropylene material according to claim 4, characterized in that: The melt flow rate of the homopolypropylene is 10-30 g / 10 min at 230° C. and 2.16 KG, and the melt flow rate of the random polypropylene is 1-30 g / 10 min at 230° C. and 2.16 KG.
8. The highly scratch-resistant and light-transmissive polypropylene material according to claim 4, characterized in that: The random polypropylene is a terpolymer of propylene, ethylene and butene, wherein the molar content of ethylene is 5-20 mol% and the molar content of butene is 3-10 mol%.
9. The highly scratch-resistant and light-transmitting polypropylene material according to claim 4, characterized in that: The polymer elastomer is one or more of ethylene-butene copolymer, ethylene-octene copolymer and hydrogenated styrene-butadiene copolymer, and has a melt flow rate of 1-30 g / 10 min at 230° C. and 2.16 kg.
10. The highly scratch-resistant and light-transmitting polypropylene material according to any one of claims 1 to 9, characterized in that: The inorganic filler is one or more of calcium carbonate, talc, mica, wollastonite and magnesium sulfate whisker.
11. The highly scratch-resistant and light-transmissive polypropylene material according to claim 10, characterized in that: The light diffuser is one or more of barium sulfate, white carbon black, and silicone light diffusers.
12. The highly scratch-resistant and light-transmissive polypropylene material according to claim 10, characterized in that: The anti-scratch agent is one or more of erucamide and organic silicone.
13. The highly scratch-resistant and light-transmissive polypropylene material according to claim 10, characterized in that: The nucleating agent is one or more of organic aromatic phosphates and dibenzylidene sorbitols.
14. The highly scratch-resistant and light-transmissive polypropylene material according to claim 13, characterized in that: The nucleating agent is at least one of NA-10 and NA-11 produced by Aidico and Millad 3905 and Millad NX8000 produced by Milliken & Company.
15. The highly scratch-resistant and light-transmissive polypropylene material according to claim 10, characterized in that: The other auxiliary agents are arbitrarily selected from antioxidants and light stabilizers.
16. The highly scratch-resistant and light-transmissive polypropylene material according to claim 15, characterized in that: The antioxidant includes a primary antioxidant and a secondary antioxidant, wherein the primary antioxidant is selected from one or more of hindered phenol antioxidants, thioester antioxidants, phenol antioxidants, and hindered amine antioxidants, and the secondary antioxidant is selected from phosphite antioxidants and thioether antioxidants.
17. The highly scratch-resistant and light-transmissive polypropylene material according to claim 15, characterized in that: The light stabilizer is one or more of a hindered amine light stabilizer, a benzophenone light stabilizer and a benzotriazole light stabilizer.
18. The highly scratch-resistant and light-transmissive polypropylene material according to claim 10, characterized in that: The peroxide is one or more of dicumyl peroxide, benzoyl peroxide, 2,4-dichlorobenzoyl peroxide, di-tert-butylcumyl peroxide, and azobisisobutyronitrile.
19. The highly scratch-resistant and light-transmissive polypropylene material according to claim 1, characterized in that: The hardening and permeability enhancing agent is a copolymer of double-bond-containing cage-type polysilsesquioxane and methyl methacrylate, nadic anhydride, and reactive monomers in a molar ratio of 1: (60-600): (5-200): (5-15); the reactive monomers are glycidyl methacrylate and / or maleic anhydride.
20. The highly scratch-resistant and light-transmissive polypropylene material according to claim 19, characterized in that: The double bond-containing cage-type polysilsesquioxane is methacryloxypropyl cage-type polysilsesquioxane.
21. The highly scratch-resistant and light-transmissive polypropylene material according to claim 1, characterized in that: The reaction conditions of the double bond-containing cage-type polysilsesquioxane, methyl methacrylate, nadic anhydride and reactive monomer are as follows: the raw materials are mixed with an initiator in a solvent, and then the temperature is raised to 70-90° C. and stirred for reaction for 10-15 hours to obtain a copolymer.
22. The highly scratch-resistant and light-transmissive polypropylene material according to claim 21, characterized in that: The initiator is one or more of azobisisobutyronitrile, benzoyl peroxide and dicumyl peroxide; the amount of the initiator is 1-10 mol% of the molar amount of the cage-type polysilsesquioxane containing double bonds.
23. The highly scratch-resistant and light-transmissive polypropylene material according to claim 1, characterized in that: The viscosity average molecular weight of the hardening and permeability enhancing agent is 50,000-500,000 Daltons.
24. The highly scratch-resistant and light-transmissive polypropylene material according to any one of claims 1 to 9, characterized in that: The light transmittance of the polypropylene material is 60-80% at a thickness of 3.0 mm, the surface pencil hardness is HB to 2H, and the cantilever beam notched impact strength is 15-50 KJ / m at 23°C. 2 , the flexural modulus is 1000-1600MPa.
25. A method for preparing the highly scratch-resistant and light-transmitting polypropylene material according to any one of claims 1 to 24, characterized in that: The following steps are involved: The polypropylene, polymer elastomer, inorganic filler, hardening and permeability enhancing agent, light diffuser, scratch resistant agent, nucleating agent, other additives and peroxide are mixed and added into a twin-screw extruder, melt-mixed and then extruded to obtain the polypropylene material.
26. The method for preparing the highly scratch-resistant and light-transmitting polypropylene material according to claim 25, characterized in that: The melt mixing conditions are: melt temperature 220-230° C., rotation speed 50-100 rpm.
27. Use of the highly scratch-resistant and light-transmitting polypropylene material according to any one of claims 1 to 24 or the highly scratch-resistant and light-transmitting polypropylene material prepared by the method according to claim 25 or 26 in automotive interior products.
Citation Information
Patent Citations
Matte scratch-resistant modified polypropylene composite material for interior trim of automobile
CN102336954A
Surface-reinforced transparent substrate and its manufacturing method
CN106062053B
High-hardness plastic
CN106589552A
A method for preparing a paint-free, scratch-resistant PP alloy material
CN107286469B
Polypropylene composite material, preparation method and application thereof
CN110903549A